Designer SiO2 Metasurfaces for Efficient Passive Radiative Cooling - Zhenmin Ding; Honglin Li; Xin Li; Xueying Fan; Juliana Jaramillo‐Fernandez; Lorenzo Pattelli; Jiupeng Zhao; Shichao Niu; Yao Li; Hongbo Xu (Advanced Materials Interfaces, 2024)
Abstract In recent years, an increasing number of passive radiative cooling materials are proposed in the literature, with several examples relying on the use of silica (SiO2) due to its unique stability, non‐toxicity, and availability. Nonetheless, due to its bulk phonon‐polariton band, SiO2 presents a marked reflection peak within the atmospheric transparency window (8‐13 µm), leading to an emissivity decrease that poses a challenge to fulfilling the criteria for sub‐ambient passive radiative cooling. Thus, the latest developments in this field are devoted to the design of engineered SiO2 photonic structures, to increase the cooling potential of bulk SiO2 radiative coolers. This review seeks to identify the most effective photonic design and fabrication strategies for SiO2 radiative emitters by evaluating their cooling efficacy, as well as their scalability, providing an in‐depth analysis of the fundamental principles, structural models, and results (both numerical and experimental) of various types of SiO2 radiative coolers.